Narratives on education for sustainable development in Malaysian universities - Syed-Abdullah, Sharifah Intan Sharina; Kushnir, Iryna; Abdrahim, Nur Aira (Multidisciplinary Digital Publishing Institute, 2023)
Higher education institutions are powerful forces in producing the human capital necessary to drive sustainable development. To support global aspirations to improve our planet, higher education institutions worldwide have been integrating the education for sustainable development agenda within the curriculum of a wide range of disciplines. This study aims to describe how Malaysian public universities have been implementing education for sustainable development. By adopting a qualitative research approach, this study gathered data through in-depth interviews and four focus group discussions with 16 sustainability experts from five public universities in Malaysia, renowned for their education provision and research in the field of sustainable development. Thematic analyses of the data reveal four prevailing approaches to implementing education for sustainable development at Malaysian higher education institutions. They are the organisational adoption approach, the competitive approach, the continuity approach, and the transformative approach. This study also projects the idea that the implementation of education for sustainable development (ESD) requires solid support from the institutions’ senior management to prioritise it in their managerial agenda.